(untitled) (Research, Society and Development, 2021)
Objective: This study aimed to investigate the effects of moderate- to high-intensity intradialytic progressive resistance training (IPRT) on muscle strength (MS), physical capacity (PC), and quality of life (QoL) in end-stage renal disease patients. Methods: Twenty-seven sedentary hemodialysis patients (55.5±10.6 years) were divided into a resistance training group (RTG, n=15) and a control group (CG, n=12). Patients of RTG were submitted to IPRT, three times per week for 12 weeks. The Borg’s scale was used for exercise prescription. Muscle strength was measured using hand grip dynamometry (MS). The sit-to-stand (STS) test and usual walking speed (UWS) test were performed to measure the physical capacity, and the SF-36 questionnaire to evaluate the quality of life (QoL). All patients were evaluated at baseline and after 12 weeks. Results: Moderate- to high-intensity IPRT significantly increased the MS (p=0.001, effect size (ES)=0.98), the physical capacity evaluated by the STS (p=0.002, ES=0.85) and UWS (p=0.014, ES=1.11), and all domains of SF-36 questionnaire (p<0.05). On the other hand, in the CG these variables did not change significantly. The protocol was well tolerated and was not associated with significant clinical complications. Conclusion: Twelve weeks of moderate- to high-intensity IPRT in HD patients was safe and improved MS, PC, and QoL.